2004
DOI: 10.1002/ptr.1493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginkgolides on β‐amyloid‐suppressed acetylocholine release from rat hippocampal slices

Abstract: As Ginkgo has been shown to improve age-related memory de fi cits and beta-amyloid-related peptides have been suggested to play a signi fi cant role in memory degeneration in Alzheimer's disease, the present study was carried out to examine the effect of two major ginkgolides, A and B, on beta-amyloid peptide-modulated acetylcholine (ACh) release from hippocampal brain slices. Addition of beta-amyloid fragment(25-35) (0.01-1 micro M) in the superfusion medium suppressed the K(+)-evoked [(3)H]-ACh release from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In a previous study it has been shown that GB but not GA suppressed the K + -evoked acetylcholine release in rat hippocampal slices treated with the Aβfragment (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [25]. Although we have found that higher concentrations of GB re-establish normal LTP and therefore this aspect of our work is consistent with these studies, GA in our experimental paradigm was also able to re-establish normal LTP.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study it has been shown that GB but not GA suppressed the K + -evoked acetylcholine release in rat hippocampal slices treated with the Aβfragment (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [25]. Although we have found that higher concentrations of GB re-establish normal LTP and therefore this aspect of our work is consistent with these studies, GA in our experimental paradigm was also able to re-establish normal LTP.…”
Section: Discussionsupporting
confidence: 93%
“…Given the limited therapeutic options for DAT, treatment with EGb still appears to be the method of choice compared with the ChE inhibitors (Schulz, 2003a). A few another studies also confirmed the role of Ginkgo biloba or its isolated constituents in dementia and other memory disorders (Pan, 2005;Haan and Horr, 2004;Yao et al, 2004;Lee et al, 2004;Kurz and Van Baelen, 2004;Evans et al, 2004;Williams et al, 2004;Colciaghi et al, 2004;Gertz and Kiefer, 2004;Kanowski and Hoerr, 2003;Stackman et al, 2003;Smith and Luo, 2003 Bars, 2003;Muller and Chatterjee, 2003;Andrieu et al, 2003;Birks et al, 2002;Nathan et al, 2002;Mix and Crews, 2002;Gasser and Gasser, 2001;Wettstein, 2000;van Dongen et al, 2000;Bastianetto et al, 2000). During recent years, several cases of hemorrhage have been reported to occur in coincidence with the use of Ginkgo products.…”
Section: Ginkgo Bilobamentioning
confidence: 94%
“…In transgenic Caenorhabditis elegans , ginkgolide A ( 5.1 ) reduced Aβ‐induced adverse behavior, including paralysis . Ginkgolide B ( 5.2 ) inversed the Aβ‐induced reduction of ACh release from hippocampal brain slices, and caused substantial improvement in learning and memory worsening by Aβ . Ginkgolide J ( 5.3 ) was described as the most potent inhibitor of Aβ‐induced hippocampal neuronal cell death among the ginkgolides in the plant extract .…”
Section: Ginkgolides and Bilobalidementioning
confidence: 99%